Effect of plant growth regulators on in vitro morphogenesis in Gladiolus (Gladiolus hybridus Hort.) from cultured corm slice - Tripathi, M. K.; Malviya, R. K.; Vidhyashankar, M.; Patel, R. P. (International Journal of Agricultural Technology, 2017)
In present research, corm slice explant of gladiolus (Gladiolus hybridus) was cultured on MS medium amended with diverse auxins and cytokinins in varying concentrations as sole as well as in different combinations. Regarding in vitro response, induction medium MS2B.5D (MS + 2.0 mgl-1 BAP + 0.5 mgl-1 2,4-D + 30.0 gl-1 sucrose + 7.5 gl-1 agar) proved well for callus initiation. MS medium supplemented with BA in range of 2.0-3.0 mgl-1 in combination with 0.5 mgl-1 NAA, 30.0 gl-1 sucrose and 7.5 gl-1 agar exhibited higher shoot proliferating efficiency, number of shoot (s) per explant and shoot of higher length. In respect to in vitro rooting response, higher root proliferating efficiency was documented on rooting medium MS.5IB.5Kn (MS + 0.5 mgl-1 IBA + 0.5 mgl-1 Kinetin + 15.0 gl-1 sucrose + 7.5 gl-1agar), while number of root (s) with higher length were recovered on rooting medium MS.5IB (MS+0.5 mgl-1 IBA+15.0 gl-1 sucrose +7.5 gl-1 agar). Phenotypically normal plantlets were acquired and subsequently transferred to pots and hardened in Environmental Growth Cabinet and Net House during initial tiring period and transferred to field successfully.